1995
DOI: 10.1007/bf02276720
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal urinary uric acid/ceratinine ratio as an additional marker of perinatal asphyxia

Abstract: Infants with perinatal asphyxia have a significantly higher urinary UA/Cr ratio. This may be used as an indicator of the severity of perinatal asphyxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
2
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 12 publications
3
16
2
1
Order By: Relevance
“…Another study by Bader et al [13] showed that UA/Cr was higher in the asphyxiated group when compared to controls. (2,06+1.12, vs. 0.64+0.48; P<0.001) which is also similar to our study.…”
Section: Discussionmentioning
confidence: 93%
“…Another study by Bader et al [13] showed that UA/Cr was higher in the asphyxiated group when compared to controls. (2,06+1.12, vs. 0.64+0.48; P<0.001) which is also similar to our study.…”
Section: Discussionmentioning
confidence: 93%
“…Results correlate with present study. 12 In study by Chen et al found that urinary UA/CR ratio was higher in the asphyxiated group compared to controls. This result supports present study.…”
mentioning
confidence: 94%
“…(6,12) These positive results may help the clinicians to identify the etiology of convulsions without history of asphyxia.…”
Section: Discussionmentioning
confidence: 95%
“…(6) Despite the increasing understanding of the mechanisms leading to and resulting from perinatal asphyxia early determination of brain damage following hypoxic ischemic events still remains one of the hardest problems in neonatal care. (1) Their clinical manifestation, their individual potentials to respond to the asphyxia insult to recover vary among the newborns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation